The Performance-based Farm Payment – a Proposal for a Paradigm Shift in the CAP - Uwe Latacz-Lohmann; Marlene Noack; Florian Tietjens (EuroChoices, 2026)
This paper proposes an agricultural policy model that underpins the CAP with a credible performance paradigm and at the same time reduces its complexity. The `Performance-based Farm Payment' links farm payments to a farm's achievement of the goals of the European Green Deal. The central element of the model is a matrix converting a given set of voluntary environmental measures into contributions to each of the Green Deal goals. Payments are made only when a farmer meets at least one of the Green Deal goals (threshold principle). The Performance-based Farm Payment is designed to replace all area-related payments of the current CAP. The practical application of the model is illustrated using a sample calculation. Besides being less complex, the Performance-based Farm Payment enables farmers to integrate the environmental sector into their operations, thus creating an additional source of income. It can also serve as an environmental benchmarking tool for farms called for in the strategic dialogue at EU level. – – In diesem Papier wird ein agrarpolitisches Modell vorgeschlagen, das die GAP mit einem nachvollziehbaren Leistungsparadigma untermauert und gleichzeitig ihre Komplexität verringert. Die ,leistungsbezogene Betriebsprämie`knüpft die Betriebsprämien an die Erreichung der Ziele des Europäischen ,Green Deals'. Das zentrale Element des Modells ist eine Matrix, die eine Reihe freiwilliger Umweltmaßnahmen in Beiträge zu diesen Zielen umwandelt. Zahlungen werden nur dann geleistet, wenn ein Betrieb mindestens eines der Ziele des erfüllt (Schwellenwertprinzip). Die leistungsbezogene Betriebsprämie soll alle flächenbezogenen Zahlungen der aktuellen GAP ersetzen. Die praktische Anwendung des Modells wird anhand eines Beispiels veranschaulicht. Die leistungsbezogene Betriebsprämie ist nicht nur weniger komplex, sondern ermöglicht es den Landwirtinnen und Landwirten auch, den Umweltbereich in ihre Betriebe zu integrieren und so eine zusätzliche Einnahmequelle zu schaffen. Sie kann auch als Instrument für das ,Umwelt-Benchmarking`von landwirtschaftlichen Betrieben dienen, das im strategischen Dialog auf EU-Ebene gefordert wird.
Keywords: 630